Analisis Pengelolaan Keuangan Desa (Kasus Di Desa Babulu Darat Kecamatan Babulu Kabupaten Penajam Paser Utara) (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
MENTARI PITANIATI. Analysis of village financial management case in Babulu Darat village sub district of Babulu, Penajam Paser Utara regency. Under guidance of Mr. Yunus Tete Konde and Mrs. Salmah Pattisahusiwa.Peraturan Menteri Dalam Negeri Nomor 113 Tahun 2014 concerning Village Financial Management, Regulate how his village financial management, consisting of the planning, implementation,administration, reporting and accountability.The purpose of this research was to determine and analyze the financial management of the village in the Babulu Darat Village according to Peraturan Menteri Dalam Negeri Nomor 113 Tahun 2014 concerning Village Financial Management. This research is an descriptive model by using comparative approach, and used observation and interview method. The required data are the result of interview dan accountability report in 2016. To analyze village financial management in Babulu Darat Village, this research used analysis tools from of regulation. The regulation are Undang-undang No. 6 Tahun 2014 concerning village and Peraturan Menteri Dalam Negeri Nomor 113 Tahun 2014 concerning Village Financial Management.The result of this research is show that financial management of the village in Babulu Darat Village has undertaken well. Implementation, administration and financial management reporting is the stage which performed better than the other stages. Planning and accountability while carried on quite well. Expected better implement Babulu Darat Village about Peraturan Menteri Dalam Negeri Nomor 113 Tahun 2014 in order to finance the management of the village could have been better.Keyword : village, village financial and village financial management